Behavioral Risk Factors of Noncommunicable Diseases Among Medical and Nonmedical Undergraduate Students of Dhaka City, Bangladesh - Rajib Mondal; Rajib Chandra Sarker; Palash Chandra Banik (Shahrekord University of Medical Sciences, 2018)
Background and aims: Behavioral risk factors of noncommunicable diseases (NCDs) are established during early age and continued into adulthood. In Bangladesh, the scenario of NCD risk factors among students was inadequately studied. The aim of this study was to assess and compare the prevalence of behavioral risk factors of NCDs between undergraduate medical and nonmedical students. Methods: This cross-sectional study was conducted among 280 undergraduate students (equal number of students from medical and nonmedical backgrounds). Respondents were selected purposively from 5 purposively-selected institutions. Modified WHO STEPS instrument was used for data collection. Respondents were asked about their behavioral risk factors (tobacco use, insufficient fruit and vegetable intake, inadequate physical activity, and alcohol consumption) by face-to-face interviews. Results: Men students were more in both groups. The mean age of the medical and nonmedical students was 22.1±2.0 and 21.8±1.9 years, respectively. Tobacco use was more among nonmedical students than that among the counterpart (22.1% vs. 15.7%). Medical students were more used to take insufficient fruits and vegetables compared to nonmedical students (97.9% vs. 93.6%). Equal proportions (71.4%) of students in both groups were used to perform inadequate physical activity. Alcohol consumption was observed more among nonmedical students (12.9% vs. 8.6%). Conclusion: Behavioral risk factors of NCDs were remarkable among students of both groups, mainly among nonmedical students.